A trusted and collaborative E-Mosque marketplace: conceptual solution - Ahmad Dahlan, Abdul Rahman; Za'ba, Huzaifah; Shahidan, Iznel; Ahmad Bakhtiar Mubarak, Muhamad Yusri; Riduan, Rahimi Rusyaidi (Eclat Research Publication, 2016)
This paper aims to analyse the relationship between sellers and customers based on before era e-commerce platform is introduced and the introduction of e-commercing platform. The e-mosque marketplace as proposed e-commerce platform serving as alternative e-commercing sites for the muslim and mosque’s community is proposed to provide additional functions and benefits such as more secure transaction, money-back guaranteed. The methodology for this paper is based on literature using the BMC and VPD framework and was tested using various kind of field experiment. Data were collected using informal interview at local mosque and online survey form for the online seller community. Findings – the interview results indicates the usage of endorser credibility that is ‘the mosque’ has improved the seller’s willingness to use the system. The problem that has prevented the seller reaching their audience, are difficulty to advertise the product and attracting the targeted user to buy the product. However, the survey unable to reach to older and mature online seller as the individual required more time and formal interview.